Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.jafc.5b01999
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Wild American Grapes with Vitis vinifera: A Metabolomics Study of Grape Composition

Abstract: We analyzed via untargeted UHPLC-ESI-Q-TOF-MS the metabolome of the berry tissues (skin, pulp, seeds) of some American Vitis species (Vitis cinerea, Vitis californica, Vitis arizonica), together with four interspecific hybrids, and seven Vitis vinifera cultivars, aiming to find differences in the metabolomes of the American Vitis sp. versus Vitis vinifera. Apart from the known differences, that is, more complex content of anthocyanins and stilbenoids in the American grapes, we observed higher procyanidin accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 49 publications
5
79
1
1
Order By: Relevance
“…Narduzzi, Stanstrup, and Mattivi () suggested that the flavan‐3‐ols in V. vinifera were monomers and polymers (dimeric and trimeric procyanidins). We observed five flavan‐3‐ols, including two monomers (epicatechin and epigallocatechin) and three gallates (epicatechin 3‐ O ‐gallate, epigallocatechin 3‐ O ‐gallate, and 4′‐ O ‐methyl‐epigallocatechin‐3‐ O ‐gallate) in all of the skins of berry ripening stages (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Narduzzi, Stanstrup, and Mattivi () suggested that the flavan‐3‐ols in V. vinifera were monomers and polymers (dimeric and trimeric procyanidins). We observed five flavan‐3‐ols, including two monomers (epicatechin and epigallocatechin) and three gallates (epicatechin 3‐ O ‐gallate, epigallocatechin 3‐ O ‐gallate, and 4′‐ O ‐methyl‐epigallocatechin‐3‐ O ‐gallate) in all of the skins of berry ripening stages (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that there were considerable differences in the flavonol regulation factors for these two grapes, of which F3′5′H and F3′H branch pathways were the principal carbon pathway synthesizing 3′,4′,5′-type and 3′,4′-type flavonols, respectively, in the skins of muscadine and V. vinifera grapes. Narduzzi, Stanstrup, and Mattivi (2015) suggested that the flavan-3-ols in V. vinifera were monomers and polymers (dimeric and trimeric procya- (Table S1). In particular, the composition in berry ripening muscadine skins was mainly made up of gallate form, whereas monomer and gallate forms in V. vinifera skins were both contained (e.g., 72.6%-100% and 0%-27.4% of the total flavan-3-ol in 2014, respectively; Table 2, Figure 4).…”
Section: Flavonol Profilesmentioning
confidence: 99%
“…In addition, their skins also had flavonols such as glycosides of quercetin, kaempferol, and myricetin [3,5]. Meanwhile, abundant flavan-3-ols like procyanidins (epicatechin and epicatechin gallate) and condensed tannins were identified in muscadine seeds [13,15,16]. However, these identifications have not been fully elucidated, and the contents varied greatly in different reports [1,10,13,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 2015, Narduzzi et al [45] compared four American wild grapes with different Vitis vinifera cultivars through an untargeted LC-MS approach. The primary results obtained from this research were related to a more complex content of anthocyanins and stilbenoids in the American grapes and a higher procyanidin accumulation in the vinifera skin and seeds.…”
Section: Study Of Plant-based Products Through the Use Of Metabolomentioning
confidence: 99%